Pengaruh Kecerdasan Emosional Stres Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan pada Perusahaan - Hadijah Hadijah; Achmad Syahruddin; Muhammad Riski (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to determine the influence of emotional intelligence, job stress, and job satisfaction on employee performance at the Limited Liability Company (PT) Nuansa Dharma Cipta Tanah Grogot. The sample in this study were all employees at PT. XYZ. The sampling technique used was total sampling, so the sample in this study was 33 employees of PT. XYZ. The results of multiple linear regression analysis obtained a regression equation, namely: Y = -8.074 + 0.875X1 + 0.092X2 + 0.152X3. The correlation coefficient (R) value is 0.965, which means a very strong correlation between emotional intelligence (X1), job stress (X2), and job satisfaction (X3) on employee performance (Y) at PT. XYZ. The coefficient of determination (Adjusted R2) of 0.925 or 92.5% indicates the significant contribution of Emotional Intelligence (X1), Job Stress (X2), and Job Satisfaction (X3) to Employee Performance (Y). The remaining 7.5% is explained by other variables not included in this study. The results of the simulants test (F test) show that the calculated F value > F table (131.862 > 2.93) so it can be concluded that together Emotional Intelligence (X1), Work Stress (X2), and Job Satisfaction (X3) have an effect on Employee Performance (Y) at PT. XYZ. Furthermore, a partial test was conducted by looking at the calculated t value of each variable consisting of Emotional Intelligence (X1), Job Stress (X2), and Job Satisfaction (X3) of 13.059, 3.370, and 5.178 respectively, which when compared with the t table of 2.04523, Emotional Intelligence (X1), Job Stress (X2), and Job Satisfaction (X3) have an individual effect on Employee Performance (Y) because the calculated t value > t table, then the Job Stress hypothesis (X2) is not proven to be dominant because the value of Emotional Intelligence (X1) is greater, which means that Emotional Intelligence (X1) has a dominant effect on Employee Performance (Y) at PT. XYZ.